Factors associated with the use of the PUSTAKA online registration service at the Sekaran Community Health Center in Semarang City - Bunga Gustikasari Ismail; Nurhasmadiar Nandini; Rani Tiyas Budiyanti (Public Health and Occupational Safety Journal, 2026)
Background: Online registration services have been implemented in community health centers to facilitate patient access and reduce long queues by enabling appointment scheduling at specific times. However, the utilization of this service in several community health centers in Semarang City remains below the monthly target of 10%. At Sekaran Community Health Center, for example, the average utilization rate was only 1.03% between June and August 2023. Objectives: This study analyzed the factors associated with the use of the PUSTAKA Online Registration Service at The Sekaran Community Health Center in Semarang City. Methods: This study employed a quantitative research design with a cross-sectional approach. The population consisted of existing patients at Sekaran Community Health Center, with a sample of 97 respondents selected using accidental sampling. The variables examined included age, education, occupation, attitude, knowledge, perceived need, availability of facilities, and ease of obtaining information in relation to the decision to use PUSTAKA services. Data were collected using a closed-ended questionnaire that had previously undergone validity and reliability testing. Results: The results of the research analysis using the chi square statistical test showed the conclusion that there was a significant relationship between the factors of age (p = 0.006), education (p = 0.007), occupation (p = 0.044), attitude (p = 0.017), perceived needs (p = 0.006), and ease of obtaining information (p = 0.021) with the decision to use PUSTAKA services at the Sekaran Health Center. Conclusions: Meanwhile, there is no relationship between knowledge (p = 0.812) and the availability of facilities (p = 0.114) with the decision to use PUSTAKA.